The interregnum controversies in world politics 1989-1999 - Cox, Michael 1947-; Booth, Ken 1943-; Dunne, Timothy 1965- (Cambridge University Press, 1999)
The Interregnum: Controversies in World Politics 1989–1999 is a series of critical reflections on the major controversies in and about world politics in the 1990s. We are living in an era which seemingly defies description: in social and political theory, our age is frequently referred to as 'post-modern'; in international relations, we remain in the 'post-Cold War' age. The age is only characterised by what it is not. This collection of critical reflections, written by leading scholars in the field, sheds light on the meanings of world politics in what we are calling The Interregnum. The central question of the Special Issue might be put as follows: what do the major controversies in world politics in the 1990s tell us about the characteristics of the age, who we are, and where world politics might be going?
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1989-1999; World politics / 1989-; Internationale Politik; Aufsatzsammlung